CO2 removal to reach net zero warming of global methane and nitrous oxide emissions of livestock: Comparison of two metrics under different 2050 FAO scenarios. - Fabio Correddu; Mondina Francesca Lunesu; Sara Sechi; Maria Francesca Caratzu; Giuseppe Pulina (PLoS ONE)
Achieving global climate targets requires accurate quantification of greenhouse gas (GHG) emissions and their implied impact on temperature. However, the choice of emission metric-particularly between Global Warming Potential over 100 years (GWP100) and Global Warming Potential Star (GWP*)-can significantly influence how emissions and their contributions to global warming are represented in climate assessments. While metrics do not alter physical temperature outcomes, they affect how emissions' impacts are interpreted, which in turn influences carbon dioxide removal (CDR) estimates and mitigation strategies. Using FAO projections for global livestock emissions to 2050, we analyze how different metric choices affect estimates of the CDR required to offset methane (CH₄) emissions and achieve no additional warming condition. Our findings highlight that GWP100 can overestimate or underestimate the cumulative warming impact of CH₄ emissions under different emission trajectories, whereas GWP* provides a dynamic approach that better aligns with temperature goals. These differences have critical implications for climate policy, as they influence the perceived effectiveness of mitigation strategies and the allocation of CDR requirements. This study underscores the necessity of selecting appropriate metrics when designing climate mitigation frameworks, particularly for methane-intensive sectors like livestock, to ensure an accurate representation of their contribution to global temperature targets.